Cytotoxic evaluation of different fractions of Salvia chorassanica Bunge on MCF-7 and DU 145 cell lines - Alireza Golshan; Elaheh Amini; Seyed Ahmad Emami; Javad Asili; Zahra Jalali; Sarvenaz Sabouri-Rad; Naghmeh Sanjar-Mousavi; Zahra Tayarani-Najaran (Wolters Kluwer Medknow Publications, 2016)
Because of antimicrobial, antioxidant, and anticancer potential, Salvia chorassanica Bunge (Lamiaceae) has been considered as a popular herb in Iranian traditional medicine. Previous studies have shown remarkable cytotoxic properties of the methanol, n-hexane and dichloromethane extract of S. chorassanica on human cervical cancer cells. To seek the therapeutic potentials of S. chorassanica, this study was undertaken to evaluate the cytotoxic activities of various extracts of this plant on human breast MCF-7 and prostate cancer DU 145 cells. The DU 145 cells were exposed to different concentrations of plant extracts (1-200 μg/ml). Cytotoxic activities were examined using alamarBlue ® assay and apoptosis was assessed by acridine orange/propodium iodide double staining and evaluation of DNA fragmentation by flow cytometry. Our findings indicated that n-hexane and dichloromethane extracts had more cytotoxic activities against DU 145 and MCF-7 cell lines compared with other extracts (P<0.05). The acridine orange/propodium iodide staining showed apoptogenic properties of n-hexane and dichloromethane extracts which was consequently confirmed by flow cytometric histogram that exhibited an increase in sub-G1 peak in treated cells as compared with untreated cancer cell lines. Taken together, these observations demonstrated cytotoxic effects of S. chorassanica extracts on MCF-7 and DU 145 cell lines which is most likely exerted via apoptosis cell death. Therefore, further investigations on S. chorassanica extracts as potential chemotherapeutic agents are warranted.